United Nations Millennium Declaration (UN New YorkUS, 2000)
Calls upon developed countries to ensure adequate resources and policy coherence, and to balance the responsibilities of developing and developed countries when reporting on development progress. Sets out the Millennium goals.
Keywords: PEACE